Twin Texts and Technology: Enhancing Algebra Instruction for Elementary Teachers - Beth R. Walizer; Carol A. Borchers (The Advocate, 2011)
Introduction: Algebra is often thought of as a course taken in high school, not a part of mathematics instruction in the elementary grades. In reality, algebra is the study of mathematics concerning structure, relations, and quantity and justifying those relationships (Blanton, 2008).